Price Discovery in Crude Oil Markets: Intraday Volatility Interactions between Crude Oil Futures and Energy Exchange Traded Funds - Ozdurak, Caner; Ulusoy, Veysel (International Journal of Energy Economics and Policy, 2020)
In this paper we investigate the integration of financial derivatives with crude oil prices. The novelty of our paper is its focus on the impact of energy related Exchange Related Funds (ETFs) on crude oil prices. In the previous studies this relationship was studied only between equity markets and crude oil markets however, ETFs are now a crucial tool for information dispersion. First, we examine price discovery of crude oil prices by utilizing causality tests. We conclude that price discovery does not flow consistently from the futures to spot markets or vice versa. The causality is mostly bi-directional from futures market to spot markets for crude oil. Coherently, futures market drives energy-based ETFs market however cross market information increases the explanation power of volatility. Secondly, we tested whether there is any interaction between price volatility, the crude oil prices and energy-based ETF markets by employing EGARCH models using 5-min data. We used three different volatility measures which are square return, Garman and Klass (1980), Rogers and Satchell (1991) and Rogers et al. (1994). Keywords: Oil Prices, Time Series, Volatility, Exchange Traded Funds, EGARCH, Granger Causality, News Impact Curves JEL Classifications: C58, G13, Q02 DOI: https://doi.org/10.32479/ijeep.9014